Influence of attitudes to social media use in professional learning on studentsâ€™ online journalism self-efficacy beliefs - Joseph Njuguna; Hellen K Mberia; Margaret Jjuuko (University of Johannesburg, 2020)
With a wide variety of easily-accessible internet tools, social media have revolutionized the way people access, create and share information. Apart from facilitating social networking, these online platforms are also considered critical enablers of professional competence development, with perceptions of their use in promoting learning â€" in a domain like journalism â€" gaining currency. Using Rwanda as a case study, this article explores studentsâ€™ attitudes towards social media use in professional learning and how these predict their self-efficacy for online journalism work. Empirical data was gathered from mass communication students from five Rwandan universities (n=143), who completed a researcher-constructed â€˜online journalism self-efficacyâ€™ (OJSE) survey. Descriptive findings indicated that the students are highly efficacious in most online journalism skills. Inferential statistical analysis demonstrate that the studentsâ€™ beliefs, feelings and actions regarding social media as professional learning tools, significantly correlated with the studentsâ€™ online journalism self-efficacy. The results disconfirm the null hypothesis that negate the existence of a significant relationship between these variables. In light of the studyâ€™s results, educators need to leverage the studentsâ€™ positive social media attitudes to enhance and innovative student-centred teaching and learning approaches â€" where learners harness the affordances of the social media tools for their professional growth. Keywords: Online Journalism, Journalism students, Attitudes, Self-efficacy, Rwanda How to cite this article: Njuguna, J., Mberia, H.K. & Jjuuko, M. 2020. Influence of attitudes to social media use in professional learning on studentsâ€™ online journalism self-efficacy beliefs. Scholarship of Teaching and Learning in the South. 4(2): 160-179. https://doi.org/10.36615/sotls.v4i2.134. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/